Limitation by Fe, Zn, Co, and B12 Results in Similar Physiological Responses in Two Antarctic Phytoplankton Species - Koch, Florian; Trimborn, Scarlett (Frontiers in Marine Science, 2019)
In many areas of the world’s ocean such as the Southern Ocean (SO), primary production is low despite an abundance of macronutrients. In these high nutrient low chlorophyll (HNLC) regions the trace metal (TM) iron (Fe) limits phytoplankton biomass and subsequently the biological carbon pump. Besides Fe, the TMs zinc (Zn), cobalt (Co), and the vitamin cobalamin (B12) have also been shown to limit biomass and/or influence plankton species composition. While the impacts of Fe limitation and, to a lesser degree of Zn and Co, on the cellular physiology of Antarctic phytoplankton have been investigated, studies focusing simultaneously on several TMs and vitamins are still lacking. This study measured the impacts of Fe, Zn, Co, and B12 limitation on the Antarctic diatom Chaetoceros simplex and Fe and Zn limitation on the Antarctic cryptophyte Geminigera cryophila. Both species responded to all limitation scenarios by reducing their growth and particulate organic carbon (POC) production rates. For both algae limitation by Fe and Zn resulted in a reduction of light harvesting pigments, a significant reduction in the photosynthetic yield (Fv/Fm) and increase in the C:N ratio. Most interestingly, with a few exceptions, limitation by one TM also resulted in a significant decrease of the cellular quotas of other TMs measured. These observations suggest that one consequence of limitation by one TM may be a secondary and perhaps more fatal limitation by another.